Can four-fermion contact interactions at one-loop explain the new atomic parity violation results? - Gusso, A. [UNESP] (Springer Nature, 2000)
We investigate the possibility that four-fermion contact interactions give rise to the observed deviation from the standard model prediction for the weak charge of cesium, through one-loop contributions. We show that the presence of loops involving the third generation quarks can explain such a deviation.